A conceptual framework for assessing the usefulness of safety interventions: a tribute to William Haddon Jr. (7th October 2012) - Salmi, LR; Lagarde, E
Abstract : Background: Haddon (1926–1985) introduced in the 60s his matrix and 10 countermeasures, and a public health approach to injury control. Integrating these tools in a more comprehensive framework should help decision making. Aims/Objectives/Purpose: To present and illustrate a framework designed to provide simple and logical steps to assess and summarise available information on safety interventions. Methods: We listed questions that are relevant to decision makers, and defined related concepts and needed information. The framework also includes an algorithm to assess available information and conclude. We illustrate the tool by assessing policies on screening for unsafe driving due to medical conditions. Results/Outcomes: To implement an intervention, a decision should document: (1) the nature and size of the issue to be solved (burden and target); (2) the objective, structure and processes of the intervention (intervention); (3) the risk/effectiveness ratio (impact); (4) the practical and financial requirements to make the intervention work (efficiency); (5) the ability to guarantee appropriate ressources to cover all current and future needs (equity); and (6) the possibility of better interventions. Policies on screening for unsafe driving fail to properly document burden, and the complexity, impact and efficiency of the intervention; equity and possible other options are never raised. Significance/Contribution to the Field: This framework could be useful to develop and promote interventions based on evidence.